Influence of diltiazem on bronchoconstriction induced by cold air breathing during exercise. Issue 8 (August 1984) - Magnussen, H; Hartmann, V; Reuss, G
Abstract : Since the calcium antagonists nifedipine and verapamil have been shown to diminish exercise induced asthma, the effect of oral diltiazem, a calcium channel blocker not previously investigated in this context, was studied. Ten patients with bronchial asthma were given 60 mg diltiazem or placebo four hours before the challenge in a double blind, randomised, crossover fashion. Exercise was performed on a cycle ergometer while the subjects were breathing cold air, resulting in a respiratory heat exchange which was similar at the two study sessions. FEV1 and specific conductance (sGaw) were recorded before and three, 10, 15, and 30 minutes after the challenge. No significant differences were found between placebo and diltiazem days in the fall of FEV1 or sGaw after exercise. Thus unlike other calcium antagonists diltiazem, in a dose of 60 mg given orally four hours before exercise, failed to protect against exercise induced asthma.